Membangun Keadilan Kewarganegaraan melalui Sinergi Nilai Islam dan Pancasila - Ammelia Anna Vhony; Sidiatafa Nur Fauziah; Annisa Nurhanifah; Alifah Nur Anisah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study addresses citizenship justice in Indonesia amid the challenging era of globalization, focusing on the conflict between Pancasila as the state foundation and the dominant Islamic values in society. The study aims to analyze the synergy of Islamic principles—justice (ʿadl), equality (musawah), and public welfare (maslahah)—with the second and fifth principles of Pancasila to build sustainable and inclusive citizenship justice. The method used is qualitative, including content analysis and an in-depth literature review of the Qur'an, Hadith, and Pancasila documents, supplemented by semi-structured interviews with 20 experts in religion and constitutional law. The findings reveal a new conceptual framework called